1995
DOI: 10.1111/1523-1747.ep12323724
|View full text |Cite
|
Sign up to set email alerts
|

The Primary Cytotoxicity in Ultraviolet-A-Irradiated Riboflavin Solution Is Derived from Hydrogen Peroxide

Abstract: The cytotoxic action of near-ultraviolet (UVA) radiation on cultured mammalian cells is dependent upon oxygen, suggesting that reactive oxygen species are involved in the cellular action of the radiation. Flavins are thought to be an important chromophore for photo-induced skin injury. Irradiation of riboflavin with UVA radiation is known to produce singlet oxygen, superoxide anions, and triplet-state riboflavin radicals, which, however, are immediately quenched by many constituents of the human skin. If the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 24 publications
4
44
0
Order By: Relevance
“…However, in combination with UVA1 irradiation, riboflavin treatment could significantly impair cellular viability. It has been shown that UVA irradiation of riboflavin generates reactive intermediate species, such as singlet oxygen, superoxide anions, triplet state riboflavin radicals, and hydrogen peroxide (33)(34)(35). High-dose UVA irradiation alone has also been proven to produce reactive oxygen species with known cytotoxic properties (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, in combination with UVA1 irradiation, riboflavin treatment could significantly impair cellular viability. It has been shown that UVA irradiation of riboflavin generates reactive intermediate species, such as singlet oxygen, superoxide anions, triplet state riboflavin radicals, and hydrogen peroxide (33)(34)(35). High-dose UVA irradiation alone has also been proven to produce reactive oxygen species with known cytotoxic properties (36).…”
Section: Discussionmentioning
confidence: 99%
“…17 Recent research has shown that the light absorption of TiO 2 can be shifted to the visible range by doping with a variety of atoms, including nitrogen, [18][19][20][21] fluorine, 22 copper, 23 and silver, 24 resulting in a new class of visible light active materials. This is of particular interest in the development of novel dental materials for two reasons: exposure of gum tissue to blue light is preferable to cytotoxic UV light 25 and most of the dental offices are already equipped with blue light sources used to cure photoactive composite dental resins. The incorporation of blue light-sensitive TiO 2 into a dental material could allow for long-term and repeatable release of antibacterial ROS.…”
Section: Introductionmentioning
confidence: 99%
“…Photosensitization occurs as a consequence of initial formation of excited states of chromophores and their subsequent interaction with substrate molecules (type I photoreaction) or molecular oxygen (type II photoreaction) through energy and/or electron transfer (9). Various chromophores contained in human skin, such as urocanic acid (10), riboflavin (11), melanin precursors (12), and advanced glycation end products (13,14) have been proposed as endogenous UV sensitizers of photooxidative stress, but molecular identity and mechanism of action of relevant endogenous skin photosensitizers remain elusive (3,15,16). Recently, we have presented evidence that skin structural proteins such as collagen and elastin and specifically their UVA chromophores represent a novel class of potent endogenous photosensitizers in human skin (13,14,17).…”
mentioning
confidence: 99%